(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Combustion systems are the least amenable of all gas turbine components to analyze. Among the literature overview made, it was realized that even though significant steps have been made in improving the combustor design procedure via the use of computational fluid dynamics, much of the design process still relies upon empirically derived rules. These rules include the calculation procedure of the required airflow rate by each zone of the combustion chamber to attain a suitable gas temperature, high values of combustion efficiency, low concentrations of pollutant species together with the determination of liner geometry that matches the chamber required performance goals with the constraints imposed by the engine dimensions [1,2,3, and 4]. The main target of this research work is to identify the proper procedure to distribute a predetermined airflow rate in annular type combustor and to generalize an effective calculation method that formulate and solve the problems in as much simplified and accurate manner as possible. The combustor dimensions and airflow rates in each zone is found in reference [5] and shown in Figure 1. It is designed with central vaporizing unit to deliver 516.3 KW of power with a geometrical constraint of 142 mm & 140 mm overall length and casing diameter, respectively, while the airflow rate is 0.8 kg/sec and the fuel flow rate is 0.012 kg/sec [5, 6].